Navigating formal, informal, and integrated seed systems: Drivers of choice by sorghum grain producers in Tanzania and implications for seed access - Muricho, Geoffrey; Gichuru, Lilian; Akpo, Essegbemon; Templer, Noel A.; Puozaa, Doris Kanvenaa; Gitonga, Zachary; Melesse, Mequanint; Mwenda, Emmanuel Thomas; Mchau, Devotha; Binagwa, Papias Hongera; Shiundu, Ibrahim; Ojiewo, Chris Ochieng (John Wiley & Sons Ltd., 2025)
Understanding what drives farmers to choose one seed system over another is important in setting goals for crop improvement programs and designing an effective seed delivery system and marketing strategy. This study used survey data from 1492 households and a multinomial logit model to analyze seed systems choice by smallholder sorghum grain producers in Tanzania. Results showed that 84% of the farmers relied on the informal seed system, 11% on an integrated seed system (involving a combination of informal and formal systems), and only 5% exclusively accessed seed through the formal system. Farmers mainly accessed information on seed, agronomy, and markets from their peers. Proximity and participation in input and output markets, financial literacy, use of crop insurance, and access to financial and extension services were associated with a high likelihood of using formal seed systems. On the other hand, limited access to agronomic, and seed information from peers, as well as long distances to main markets, were associated with the use of informal seed systems. The integrated system was associated with intercropping and willingness to experiment with new ideas and technologies. Making sufficient quantities of quality seed available to farmers at the last mile through various channels, improving farmers' access to financial services, and developing multiple stress-tolerant varieties can enhance the use of improved varieties and formal channels of seed access. We recommend innovative ways of moving sufficient quantities of quality seeds of improved varieties through the informal seed system in the interim while further developing the formal system in the long run.